Porque os doutores possuem em suas cozinhas panos de prato adornados com pontilhas de crochê... - Carvalho, Sandra Helena Escouto de (1998)
This work consisted of an investigation of the ethnographic type, concerning the textile practices of the crochet as cultural expression of resistence. In this perspective, sought to understand tem in its ritual processes of transmission, learning and significance, in the ambit of the informal education....